2017
DOI: 10.1016/j.meegid.2017.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in the C-terminus of merozoite surface protein 1 among Plasmodium knowlesi isolates from Selangor and Sabah Borneo, Malaysia

Abstract: Plasmodium knowlesi, a malaria parasite of macaques, has emerged as an important parasite of humans. Despite the significance of P. knowlesi malaria in parts of Southeast Asia, very little is known about the genetic variation in this parasite. Our aim here was to explore sequence variation in a molecule called the 42kDa merozoite surface protein-1 (MSP-1), which is found on the surface of blood stages of Plasmodium spp. and plays a key role in erythrocyte invasion. Several studies of P. falciparum have reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 48 publications
4
24
2
Order By: Relevance
“…The 165 singleton variable sites were detected indicated that new and rare variant were present indicating population expansion however, Li and Fu’s D* and F* did not show significant negative values. Overall, the full-length gene showed significant negative selection (− 7.43, P < 0.000) and similar significant negative selection has been recently reported for invasion genes pknbpxa , pkmsp3 , and pkmsp1 [ 27 29 ]. The phylogenetic tree showed separation of the P. knowlesi MSP1P isolates from Malaysian Borneo into 2 clusters while the laboratory lines from Peninsular Malaysia formed a third cluster.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The 165 singleton variable sites were detected indicated that new and rare variant were present indicating population expansion however, Li and Fu’s D* and F* did not show significant negative values. Overall, the full-length gene showed significant negative selection (− 7.43, P < 0.000) and similar significant negative selection has been recently reported for invasion genes pknbpxa , pkmsp3 , and pkmsp1 [ 27 29 ]. The phylogenetic tree showed separation of the P. knowlesi MSP1P isolates from Malaysian Borneo into 2 clusters while the laboratory lines from Peninsular Malaysia formed a third cluster.…”
Section: Discussionsupporting
confidence: 81%
“…A recent study showed that polymorphisms within the merozoite invasion genes (normocyte binding protein xa and xb , nbpxa and nbpxb ) of P. knowlesi were linked to hyperparasitaemia and disease severity in human infections [ 26 ]. Potential vaccine candidates like Duffy binding protein (DBP), merozoite surface protein (MSP) 1 and 3, normocyte binding protein xa have recently been studied from P. knowlesi clinical isolates [ 27 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hitherto, proteins of P. knowlesi involved in invasion of erythrocytes are generally under purifying (negative) selection ( Table 1 ), in most cases different from those of P. vivax and P. falciparum . 73 83 Negative selection may imply that the genes are under functional constrains. At the same time, the mutations are deleterious to the parasite and the P. knowlesi population is screening for best-adapted variants.…”
Section: Molecular Epidemiology and Diversitymentioning
confidence: 99%
“…A recent P. knowlesi study showed association of polymorphisms within the merozoite invasion genes (normocyte binding protein xa and xb , nbpxa and nbpxb ) with high parasite counts and disease severity in human infections [ 17 ]. A number of blood stage antigens like Duffy binding protein (DBP), merozoite surface protein 1 (MSP-1), MSP-1 paralog, MSP-3 and nbpxa have very recently been studied from P. knowlesi clinical isolates but none has been shown to be under positive natural selection [ 18 21 ].…”
Section: Introductionmentioning
confidence: 99%